Guidelines for mapping the preferences in gender sensitive product profiles to crop ontology and creating a consumer segment ontology. Version 1.0. - Arnaud, Elizabeth; Khamila, Sylvhia; Kibooga, Charity; Ndagire, Lilian Yiga; Marimo, Pricilla (2022)
The guidelines were developed to guide scientists, database managers and ontology curators to annotate their product profiles with the ontology the proper social dimensions, documenting trait preferences in a way that it can be interpretable by breeders and food scientists. The development of breeding product profiles targeting specific market segments or consumer segments supposes that breeders can access interpretable information about the key preferences of the end users. The translation or interpretation of the collected preferences into traits and variables to make it interpretable and measurable by breeders is not always straightforward. A lot of contextual information needs to be included.